Analisis Manajemen Pendistribusian Zakat Infaq Shodaqoh di Baitul Maal Hidayatullah dalam Mensejahterakan Masyarakat di Masa Pandemi Covid-19 - M. Soleh Mauludin; Ayu Wulandini Putri Pratama (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
This study aims to find out the extent of distribution of ZIS is able to improve the welfare of individuals who are entitled to receive during the Covid-19 pandemic. By using qualitative approach and theory of community welfare, the research that took the object of research in Baitul Maal Hidayatullah resulted in the conclusion that the distribution of ZIS is able to improve the welfare of recipients in terms of materials, such as foodstuffs and so on. In addition, it is also able to improve spiritual well-being which includes morals, ethics, harmony of adjustment, and so on. However, the distribution of ZIS has not been able to improve welfare in mental aspects, such as educational facilities, cultural environment.